Clinical, Histologic, and Computed Tomographic Features of Oral Papillary Squamous Cell Carcinoma in Dogs: 9 Cases (2008–2011). (March 2013) - Soukup, Jason W.; Snyder, Christopher J.; Simmons, Betsie T.; Pinkerton, Marie E.; Chun, Ruthanne
Medical records of dogs diagnosed with oral papillary squamous cell carcinoma between December 2008 and April 2011 were reviewed. Information abstracted included signalment, tumor location, tumor size, computed tomographic (CT) features, evidence of metastatic disease based on cytologic examination of lymph node aspirates and thoracic radiography, treatment, surgical margins, histologic features, and treatment outcome. Dogs included in the study were all sexually altered, predominantly large breed dogs with a mean age of 3.9-years (range, 0.5 to 9.0-years). The most common location was the rostral maxilla. Invasion of underlying bone and lymphadenopathy were evident on CT imaging in most dogs. No evidence of metastasis was found on mandibular lymph node cytology and thoracic radiography. Histologic analysis revealed similar morphologic findings for all surgically resected tumors. Surgical excision with 1–2 cm margins was complete in all cases, with a mean tumor-free interval of 12.1-months.